A novel low shrinkage dimethacrylate monomer as an alternative to BisGMA for adhesive and resin-based composite applications - Fernanda Sandes de LUCENA; Matthew LOGAN; Steven LEWIS; Neil DEATHERAGE; Adilson Yoshio FURUSE; Carmem Silvia PFEIFER (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of this study was to develop a mixture of dimethacrylate isomers (PG6EMA) as a potential monomer for dental adhesives and composites. PG6EMA was synthesized de novo and characterized in the presence of ethanol (3%, 6% or 9%). BisGMA/TEGDMA (BTEG, 50/50 wt.%) was used as the resin control. Composites were formulated with 60 wt.% of either PG6EMA or BisGMA (40 wt.% TEGDMA and 70 wt.% filler). DMPA (0.2 wt.%) and DPI-PF6 (0.4 wt.%) were added as photoinitiators, irradiated with a mercury arc lamp (320-500 nm, 500 mW/cm2; Acticure). All materials were tested for polymerization kinetics (near-infrared), viscosity (η) and storage modulus (G', oscillatory rheometry). The composites were further characterized for water sorption/solubility, wet/dry flexural strength/modulus and polymerization stress. Data were analyzed with one-way ANOVA/Tukey's test (α = 0.05). The PG6EMA resins showed lower rates of polymerization compared with BTEG (p = 0.001) but high degrees of conversion (p = 0.002). Solvent concentration did not affect RPMAX but the 6% and 9% mixtures showed higher final DC, likely due to reduced viscosity. PG6EMA had much higher viscosity than BTEG (p <0.001) and lower G' (p = 0.003). Composites modified with PG6EMA have slower polymerization rates (p = 0.001) but higher final DC (p = 0.04) than the control. PG6EMA/TEGDMA showed lower dry/wet flexural strength and comparable dry modulus. The PG6EMA/TEGDMA composite showed a 18.4% polymerization stress reduction compared to the BTEG composite. Both base monomers had similar WS/SL and G'. Within its limitations, this study demonstrated that the newly synthesized PG6EMA was a viable alternative to BisGMA in dental composites.